2016
DOI: 10.18632/oncotarget.11657
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib and polypharmacy in very old patients with chronic myeloid leukemia: effects on response rate, toxicity and outcome

Abstract: BackgroundAbout 40% of all patients with chronic myeloid leukemia are currently old or very old. They are effectively treated with imatinib, even though underrepresented in clinical studies. Furthermore, as it happens in the general population, they often receive multiple drugs for associated chronic illnesses. Aim of this study was to assess whether or not in imatinib-treated patients aged >75 years the exposure to polypharmacy (5 drugs or more) had an impact on cytogenetic and molecular response rates, event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Postoperative outcomes (e.g., postoperative complications, delirium, extended hospital stay, and emergency department visit after cancer surgery) were evaluated in 11/47 studies (23%; Table ) . Chemotherapy‐related outcomes, such as chemotherapy‐related toxicities, chemotherapy completion, hospitalization after chemotherapy, complete remission (CR), chemotherapy dose reductions or delay, and blood transfusion, were evaluated in 12/47 studies (26%; Table ) . Frailty, falls, and physical and functional outcomes were evaluated in 7/47 studies (15%; Table ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative outcomes (e.g., postoperative complications, delirium, extended hospital stay, and emergency department visit after cancer surgery) were evaluated in 11/47 studies (23%; Table ) . Chemotherapy‐related outcomes, such as chemotherapy‐related toxicities, chemotherapy completion, hospitalization after chemotherapy, complete remission (CR), chemotherapy dose reductions or delay, and blood transfusion, were evaluated in 12/47 studies (26%; Table ) . Frailty, falls, and physical and functional outcomes were evaluated in 7/47 studies (15%; Table ) .…”
Section: Discussionmentioning
confidence: 99%
“…Frailty, falls, and physical and functional outcomes were evaluated in 7/47 studies (15%; Table ) . Survival outcomes were assessed in 12/47 studies (26%; Table ) . Other outcomes (e.g., medication adherence, caregiver burden and alternative medications use; supplemental online Table 3) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug‐drug interactions are a challenge to administering TKI therapy in older CML patients . A study conducted on 296 patients from 35 Italian Institutions showed that polypharmacy (≥5 drugs) in very old CML patients (aged ≥75 years) treated with imatinib did not alter the dosage, cytogenetic and molecular responses, or hematologic and extra‐hematologic toxicity compared with patients without polypharmacy …”
Section: Ponatinib In Chronic Myeloid Leukemiamentioning
confidence: 99%
“…Notably, to this point, such studies have not shown polypharmacy to be a risk factor for poorer CML-related outcomes among elderly patients. 63 Factors associated with the long-term burden of CML, including treatment satisfaction and adherence, and the impact of chronic AEs on quality of life can be informed by RWE studies. 2,38 The potential utility of RWE studies in this regard is highlighted by the development of the MD Anderson Symptom Inventory for CML, a questionnaire used for evaluating a patient's quality of life.…”
Section: Weaknesses and Challenges Associated With Rwementioning
confidence: 99%